1988
DOI: 10.3382/ps.0671568
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Level of Campylobacter jejuni in Broiler Processing

Abstract: The distribution and level of Campylobacter jejuni throughout broiler processing was evaluated. Six trials were conducted at three broiler processing plants to determine the occurrence of C. jejuni on commercial broilers as affected by specific processing functions. Counts were determined at specific sampling stations throughout the plants, and patterns of counts among sampling stations and plants were observed. Between 1,100 and 5,500 C. jejuni/1,000 cm2 skin surface (represents half the skin surface area of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
52
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(58 citation statements)
references
References 6 publications
5
52
0
1
Order By: Relevance
“…During the slaughter process an increase in carcass contamination is observed especially during evisceration where the potential exists for transferring intestinal microflora [15,16]. Recent evidence indeed suggests that contaminated faeces escape from the cloaca during defeathering in the slaughterhouse, which leads to a higher broiler carcass contamination [17].…”
Section: Introductionmentioning
confidence: 97%
“…During the slaughter process an increase in carcass contamination is observed especially during evisceration where the potential exists for transferring intestinal microflora [15,16]. Recent evidence indeed suggests that contaminated faeces escape from the cloaca during defeathering in the slaughterhouse, which leads to a higher broiler carcass contamination [17].…”
Section: Introductionmentioning
confidence: 97%
“…However, the causes of the differences were not fully identified. Campylobacter concentrations change along the processing line with typically a decrease after scalding and chilling, an increase after defeathering and an increase or no change after evisceration (Berrang and Dickens, 2000;Izat et al, 1988;Klein et al, 2007;Oosterom et al, 1983;Rosenquist et al, 2006;Seliwiorstow et al, 2012;Tchórzewska et al, 2013). It has not been investigated whether these changes in concentrations are maintained at similar levels between batches and between slaughterhouses.…”
mentioning
confidence: 94%
“…Survival is due to a change in the skin surface as a result of scalding temperatures, facilitating the firm attachment of bacteria [5]. Yet, Izat and his colleagues found a significant reduction of Campylobacter counts (1.84 logs) and concluded that the scalding operation is the most effective process for decreasing overall microbial levels on the surface of poultry carcasses [4]. However de-feathering, evisceration and harvesting of giblets brought an increase in carcass contamination.…”
mentioning
confidence: 99%